Transforming Employment-Oriented Adult Education to Foster Arendtian Action: Rebuilding Bridges Between Community and Vocational Education. (May 2015) - Kreber, Carolin
"Vocational education" and "community education" have evolved into largely separate fields. Bridges are reconstructed by adopting a view of vocation that recognizes the meaning people find in their work and the public value of the work they do. While these considerations underpin recent initiatives to revive a civic spirit among the "professions, " it is suggested that they apply across a much wider spectrum of occupations. Arendt's theory of action serves as a lens from which to inquire into the nature of vocational practice when enacted as public and democratic deliberation with members of the community on important issues affecting their lives. The author concludes that, appropriately understood, vocational practice includes the facilitation of Arendtian action, thereby constituting a form of community education. The author furthermore suggests that modelling types of public pedagogy characteristic of community education would enrich vocational education and help foster practitioners' capacity to act as civic agents.